Система освіти дорослих Угорщини і Данії - Орос Ільдіко; Orosz Ildikó; Oros Ildiko (Бердянський державний педагогічний університет, 2018)
Резюме. Метою роботи є схарактеризувати організацію освіти дорослих у Угорщині і Данії. З’ясовано, що в Угорщині здійснюється освіта дорослого населення з метою забезпечення грамотності відповідно до вимог ринку та розвитку економіки країни. В Угорщині створено Асоціацію підприємств підготовки дорослих, яка відіграє важливу роль у професійному нагляді та гарантії виконання вимог, а також у розвитку законодавства професійної підготовки. Для країни характерна децентралізація управління освітою незайнятих громадян. На основі концепції: державної системи професійної підготовки, перепідготовки та підвищення кваліфікації незайнятого населення; концепції освіти дорослих у країнах ЄС здійснюються програми для дорослого населення. Вища освіта в Угорщині представлена більш, ніж 20 навчальними закладами: університетами та інститутами (коледжами). Система освіти дорослих Данії становить розгалужену мережу приватних, громадських, муніципальних і державних організацій і закладів, що пропонують широкий спектр програм неформальної і формальної, професійної і непрофесійної освіти, які регулюються відповідним законодавством. Завдання в галузі освіти дорослих у Данії полягає в тому, щоб підтримувати такі тенденції у світі, які сприяють процвітанню нації: розвиток інноваційних процесів і підвищення якості навчання; підвищення гнучкості і відповідальності шкіл перед дорослими учнями. Освіту дорослих у Данії, фінансовану державою, умовно можна поділити на 3 складові: ліберальна (Вільна) освіта дорослих (народні вищі школи, школи домашньої економіки, вечірні школи, денні народні школи); загальна освіта дорослих (центри освіти дорослих, мовні центри, вечірні школи вищого рівня середньої освіти); професійно орієнтована освіта і підготовка дорослих (центр з підготовки робочої сили, виробничі школи, професійні школи, соціальні і медичні школи та ін.). Для підтримки обдарованих учнів створена система грантів (стипендій). Деякі університети та інші заклади вищої освіти надають свої власні стипендії. Значна увага в країні приділяється освіті дорослих, що здійснюється у формі загальноосвітніх курсів народних середніх шкіл, курсів професійного навчання. Піклування держави про надання всіляких послуг у системі освіти дорослого населення сприяє високим досягненням Данії у розвитку економіки. Заклади вищої освіти цієї країни дають можливість отримати не просто освіту, а знання, які стануть у нагоді не лише випускнику, а і всій країні.

Abstract. The purpose of the work is to characterize the organization of adult education in Hungary and Denmark. It has been found that in Hungary adult education is being conducted to ensure literacy in accordance with market requirements and economic development of the country. The Hungarian Association for Adult Learning has been set up in Hungary, which plays an important role in professional supervision and job satisfaction, as well as in the development of vocational training legislation. The country is characterized by decentralization of education management of unoccupied citizens. On the basis of the concept: the state system of vocational training, retraining and retraining of the unemployed population; the concept of adult education in the EU countries programs for the adult population. Higher education in Hungary is represented by more than 20 educational institutions: universities and institutes (colleges). Denmark's adult education system is an extensive network of private, community, municipal and state organizations and institutions offering a wide range of informal and formal, professional and non-professional education programs that are governed by relevant legislation. The Danish adult education task is to support world trends that promote the nation's prosperity: the development of innovative processes and the improvement of the quality of education; increasing the flexibility and responsibility of schools to adult students. The adult education in Denmark, funded by the state, can be divided into three components: liberal (Free) adult education (popular higher schools, home economics schools, evening schools, day schools); general education of adults (adult education centers, language centers, evening high schools of secondary education); professionally oriented education and adult education (labor training center, production schools, vocational schools, social and medical schools, etc.). A system of grants (scholarships) was created to support gifted students. Some universities and other institutions of higher education provide their own scholarships. Much attention in the country is paid to the education of adults, which is carried out in the form of general secondary schools courses, vocational training courses. The state's care of providing all kinds of services in the education system of the adult population contributes to Denmark's high achievements in economic development. Higher education establishments of this country give an opportunity to get not only education but also knowledge that will be useful not only for the graduate but also for the whole country.
Adults educational system of the Hungary and Denmark
http://nbuv.gov.ua/UJRN/nzbdpu_2018_3_8
Keywords: Асоціація підприємств підготовки дорослих; освіта дорослих; Угорщина; Данія; неформальна освіта; формальна освіта; професійна освіта; непрофесійна освіта; adult education; Hungary; Denmark; Association of adult education enterprises; non-formal education; formal education; vocational education; nonvocational education